Documenting a Crisis: How Postsecondary Institutions Addressed DACA Students after Trump's Rescission. Issue 5 (May 2019) - Taylor, Z. W.; Barrera, Myra C.
Background/Context: On September 5, 2017, U.S. President Donald Trump ordered an end to former President Barack Obama's 2012 immigration policy of Deferred Action for Childhood Arrivals (DACA), placing some 800, 000 undocumented immigrants—including thousands of postsecondary students—in danger of deportation. Mere hours after President Trump's announcement, postsecondary leaders across the United States began releasing official statements in support of DACA. Aside from a postsecondary institution's extolling of core values, it is important to investigate how these official institutional statements addressed the most critical, at-risk constituency on their college campus: DACA students themselves. Purpose: The purpose of this study was to analyze post-DACA rescission statements made by executive leaders of U.S. institutions of higher education to learn whether these statements addressed the most important audience of these statements—DACA students—and whether institutions of higher education provided these students the resources they needed in their time of crisis. Research Design: The data were collected from each institution of higher education's website from September 5 to September 7, 2017. The sample included 218 official institutional (two-and four-year, public and private) statements made by executive leaders at these institutions. Data analysis included deductive attribute coding and quantitative content analysis techniques such as average word count and grade-level readability measures. Findings: The post-DACA rescission statements greatly varied in length (longest = 1, 118 words; shortest = 50 words) and were unreadable by postsecondary students of average reading ability, as the average statement was written above the 15th-grade reading level. Only 54% of all statements addressed DACA students, with negligible variance (0.5%) between public and private institutions. Only 51.9% of all statements provided resources for DACA students. Of those statements, 99.1% of resources were institution-provided, whereas 20.4% were community-provided, with private institutions (12.9%) offering more community-provided resources than public institutions (7.5%). Conclusions: Institutions of higher education may want to consider best practices when composing crisis communication, primarily that crisis communication should focus on addressing the populations most affected by the crisis. Once the crisis communication is composed, that communication could be audited for its readability by the intended audience. Moreover, institutions of higher education may learn from the Virginia Tech massacre and apply it to their crisis management and communication strategies, namely by providing both institution-based and community-based resources to those most affected by the crisis. Finally, institutions of higher education may consider differentiating their crisis communication across multiple platforms such as social media, email, text message, and their institutional website to ensure that all stakeholders are aware of the potential solutions and resolutions to the crisis, in order to avoid miscommunication and a lack of organizational transparency while maintaining organizational integrity and honesty.